An innovative biologic recycling process of leukoreduction filters to produce active human antimicrobial peptides. Issue 5 (10th October 2013) - Vossier, Ludivine; Leon, Fanny; Bachelier, Cécile; Marchandin, Hélène; Lehmann, Sylvain; Leonetti, Jean‐Paul; Brodolin, Konstantin; Coste, Joliette; Fournier‐Wirth, Chantal
<x xml:space="preserve">Abstract</x> Background Human neutrophil peptides (HNPs) 1 to 3 are the major antimicrobial peptides of the azurophilic granules of neutrophils. They represent an important arm of the innate immune system. Their production by chemical synthesis and recombinant technologies is expensive and limited by technical constraints due to their composition and the presence of three disulfide bonds. Study Design and Methods We have developed an original approach based on the purification of the natural human defensins HNPs 1 to 3 from neutrophils trapped on leukoreduction filters used in blood processing. The purification of HNPs 1 to 3 from these filters is performed in two steps: extraction of HNPs 1 to 3 retained in the filters followed by their immunoprecipitation. Studies were performed to determine the stability of defensins in the filters stored at room temperature. The activity of HNPs 1 to 3 obtained by our rapid protocol was validated by determining minimal inhibitory concentrations (MICs) against six reference bacterial strains and 12 clinical isolates. Results The human defensins HNPs 1 to 3 extracted from leukoreduction filters displayed high antimicrobial activity against tested strains, with MIC values between 0.12 and 1 μg/mL. Kinetics assays showed the appearance of activity 15 minutes after peptide addition. Moreover, we found that the HNPs 1 to 3 purified from leukoreduction filters that had been stored for 45 days at room temperature remained active. Conclusion Leukoreduction filters provide a rich and safe source of active human defensins HNPs 1 to 3. Moreover, the stability of the peptides in filters stored at room temperature allows envisaging a large‐scale development of the process.